The effect of ingredient properties, liquid system and mix time on uniformity of mix and testing of uniformity of mix - Saensukjaroenphon, Marut (Kansas State University, 2016)
The uniformity of a feed mixture is determined from the coefficient of variation (CV) of ten samples in a single batch of feed. The feed industry standard is a %CV of less than 10 using a single source tracer such as salt, trace minerals or iron filings. The uniformity of mix can be affected by many factors including ingredient properties, equipment design, mix time, sampling method, sample preparation and overall precision of method. The objectives of this thesis were to verify the chloride ion test by the Quantab® chloride titrator method and to determine the effect of extended mixing time, salt particle size, sample preparation, wet mix time, spray condition, application time of the liquid addition, percent liquid addition and mixer type on the uniformity of mix. The first experiment evaluated the effect of water temperature, technician, extraction time, dissolution time on the chloride ion test by the Quantab® chloride titrator method. The salt concentration was significantly affected by water temperature and dissolution time. The results of Experiment 1 demonstrated the 60ºC water temperature and the 30 s extraction time by stirring followed by immediately placing the strip into the solution after extraction should be used for the Quantab® chloride titrator method. The second experiment evaluated the effect of extended mix time, particle size of salt and sample preparation on the %CV. The extended mix time did not result in segregation (P > 0.30). However, particle size of the salt and sample preparation significantly affected the uniformity of mix. The results of Experiment 2 indicated that the extended mix time of up to 60 minutes did not increase the %CV of the feed; the particle size of the salt used in the uniformity of mix test can significantly change the results of the test; and grinding the sample prior to analysis improved the precision of the Quantab® chloride titrator method when coarse salt is used in the manufacturing process. The third experiment evaluated the effect of wet mix time and the timing of the liquid addition using different spray conditions on the %CV. The wet mix time significantly changed the %CV of the mixture (P = 0.0057). The use of a spray nozzle had no effect on the %CV of the feed mixture when a 1.14% of a 23% saline solution was sprayed on to the feed (P = 0.7435). The results of Experiment 3 indicated the wet mix time had a greater influence on the uniformity of mix than the type of nozzle used to apply the liquid; and the shorter liquid application time allowed more time for the mechanical shear of the ribbons and paddles to break up the agglomerated wet particles and distribute them throughout the feed mixture when the total time of the liquid addition plus wet mix time was fixed. The fourth experiment evaluated the effect of different percent liquid addition, application time and mixer type with different wet mix times on the uniformity of mix. The %CV of feed mixed using a fixed wet mix time setting did not change when the percent liquid addition was increased, while the %CV of the feed mixed using a fixed total liquid mix time setting increased when increasing the percent liquid addition. The %CV of feed mixed with a ribbon mixer did not change when the liquid application time was decreased while the %CV of the feed mixed with a paddle mixer increased when decreasing the liquid application time. Differences were observed in the %CV based on the parameters of liquid cycle time, mixer type and mixer size. The results of Experiment 4 indicated the liquid addition time and the percent of liquid addition affected the uniformity of mix. The uniformity of liquid application should be tested with the highest percent liquid addition. Furthermore, application and wet mix times should be determined for each mixer type and size to establish the optimal batch cycle.
Keywords: mix time; particle size; liquid addition; wet mix time; Quantabuniformity of mix